PURWARUPA ALAT TELEMONITORING KEAMANAN RUANGAN MENGGUNAKAN IDENTIFIKASI SIDIK JARI BERBASIS INTERNET OF THINGS - Wahyu Kusuma Raharja; Bagas Santoso (LPPM Poltek ST Paul, 2020)
Human needs storage of documents or valuables requires a place that has good security from the act of others from theft. The storage area can be in the form of a safe or room. One way to increase the security of the room in a building is by creating a monitoring tool that is controlled remotely using the internet network. In addition, you can also use a fingerprint sensor that can identify users who leave or enter the room. This study aims to produce a prototype room security monitoring system with fingerprint identification using the internet network for data transfer processes on a web database. The tool is designed and built using a fingerprint sensor and push button as an input block, Arduino uno and nodemcu esp8266 as a process block, servo motor, relay, solenoid and 16x2 LCD as outputs to be connected to form a circuit. This research succeeded in designing and building a room security monitoring tool prototype using fingerprints based on the internet of things. The results of room user data record information are displayed on the website with the address http://home-guard.000webhostapp.com/index.php. Based on the testing of this tool using a fingerprint sensor can detect fingerprints both registered and unregistered. The results of the time delay testing from the fingerprint detection sensor process until the information entered on the display on the website is an average of 2.25 seconds